The body of the graphic designer and the semiotic corpus. Method notes on Stefan Sagmeister's designs - Festi, Giacomo (E|C, 2020)
The semiotic methodology, after reaffirming the practical nature of research, should open a reflection about its own being a project, even if with a scientific vocation, in a non-dissimilar manner to what happens to the disciplines of design, like applied graphics. The quality of a project firstly depends on the ability to characterize some axes of problematization, to be built in an intra- and inter-disciplinary discourse. After an exploration of the sporadic encounters between graphics and semiotics, the establishment of a research project on the work of art director and graphic designer Stefan Sagmeister is discussed, favored by the exceptional conditions of accessibility to the corpus of his projects. Alongside purely methodological problems, touching the relationship between graphical output of textual type and design practice intended as a course of action, more interpretative problems are faced, concerning the connections between authorial identity and design heterogeneity. The Austrian designer refused a “signed” identity, marked by recurrent elements and easy to identify (his motto “style = fart” is notorious), what is leaving room to an ethical dimension in his works. Some lines of propagation of it are followed in an initial analysis.